Documenting a 20th century wooden vessel at risk: the AGIOS SPYRIDON project - Katsouri, Irene; Abate, Dante; Nicolaou, Constantinos; Damianidis, Kostas; Secci, Massimiliano; Demesticha, Stella; Tzavaras, Georgios; Faka, Marina (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
Agios Spyridon, a 24 m long wooden vessel, was built in 1950, and operated in Cyprus as a trawler until 2004. Between the years 2005 and 2019 it remained on dry land, exposed to the elements. It suffered severe damages and the local authorities decided that it should be destroyed. To mitigate the consequences of its unavoidable loss, a project of controlled destruction took place in 2019, led by the University of Cyprus. Applying a rescue excavation approach, the vessel was fully recorded, using both conventional and digital methods. The project also included activities for raising public awareness for the protection of maritime heritage, as well as plans for future display of rescued components of the ship’s hull and gear.